The development of electromobility in the aspect of the energy infrastructure condition assessment - Gutsche Jan; Muślewski Łukasz; Dzioba Anna; Kolar Davor (MATEC Web of Conferences, 2021)
Electric vehicles are considered emission-free. However, having high-emission and a high degree of electricity demand coverage infrastructure, these vehicles should be considered as internal combustion cars. The purpose of the analysis carried out in this study is to present the state of energy infrastructure in Poland, to determine losses related to energy transmission and greenhouse gas emissions to the atmosphere in relation to unit consumption. Analyzing the data obtained, the emission of the electric vehicle was compared to that of a vehicle powered by diesel oil and fuel with the addition of a biocomponent.